THE RELATIONSHIP BETWEEN STRESS LEVEL AND SITTING DURATION WITH COMPLAINTS OF LOWER BACK PAIN - Dean Nur Aswitiyah Winganti; Erna Setiawati; Rahmi Isma Asmara Putri (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2025)
Background: Low Back Pain (LBP) is the most complained of musculoskeletal problem in the world. One of the factors causing low back pain is stress. Medical students are at high risk of experiencing LBP due to several factors such as high stress levels, study hours, and lack of physical activity. Another factor causing LBP is sitting for too long. Medical students usually spend >7 hours studying per day. Poor stress levels and long periods of sitting can cause complaints of low back pain in students. Aim: To determine the relationship between stress levels and long periods of sitting with complaints of low back pain in general medical students at Diponegoro University. Methods: This research is a cross-sectional study. Stress levels were measured using the Depression Anxiety Stress Scales 42 (DASS 42) and low back pain was measured using the Modified Oswestry Low Back Pain Disability Questionnaire. Spearman's rank correlation was used in bivariate analysis. The results were significant if the p-value <0.05. IBM SPSS Statistics software was used for statistical analysis in this study. Results: The Spearman correlation test showed significant results (p<0.001) with a moderate degree (r=0.471) between stress levels and complaints of low back pain. The Spearman correlation test showed significant results (p=0.027) with a weak degree (r=0.259) between sitting time and complaints of LBP. Conclusion: There is a relationship between stress levels and long periods of sitting with complaints of lower back pain in Medical students at Diponegoro University.Keywords: low back pain, stress level, sitting duration